Sharia Banking Accounting: A Study of Posting Theory on the Sharia Banking Balance Sheet - Robi Anwar; Sherin Meliana (Sharia Economic and Management Business Journal (SEMBJ), 2023)
Islamic bank accounting is a financial calculation process starting from collecting funds to channeling funds. Every collection of funds carried out by Islamic banks has accounts that are different from conventional banks, such as the collection of financial accounting reports at Islamic banks (balance sheet). The method used is library research, namely collecting data or scientific papers related to the object of research or collecting data that is literature.